PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA USAHA KECIL DAN MENENGAH PADA DISTRIK AIMAS KABUPATEN SORONG - Susana Magdalena Welly Muskita; Ratna Rosmauli Pakpahan; Arce Yuliat Ferdinandus (JURNAL BADATI, 2024)
The current condition of the business world requires companies to take strategic steps towards the future after the economic crisis. One of the potentials in each region is the existence of Small and Medium Enterprises (SMEs). Small and Medium Enterprises (SMEs) have a very important role in the national economy. Entrepreneurial orientation is known as a new approach in the renewal of company performance. The performance of Indonesian SMEs also has weaknesses in terms of the growth of the goods-producing sector (tradable) which is still low when compared to the service sector (nontradble). In fact, ideally the goods-producing sector should be higher when compared to the service sector because the goods-producing sector can be used as one of the components of national exports. The results of the validity and reliability test show that all statements in each variable are declared valid and reliable. It can be seen that rcalculate rtable (0.235) then all statement items are declared valid, while the reliability test for all variables is declared reliable because the value of Cronbach Alpa 0.60. The test results are partially obtained with a significance value of 0.000 at a significance level of 5% where the value of 0.000 0.05 then the accepted hypothesis means that entrepreneurial orientation has a partial effect on the performance of SMEs. When viewed from the calculated t value of 1.677 because the tcount is 7.634 ttable 1.677, it means that entrepreneurial orientation has a positive effect on the performance of SMEs.